KAJIAN BERTAHAN HIDUP PEMULUNG DI TEMPAT PEMBUANGAN AKHIR SAMPAH KELURAHAN SUMOMPO KECAMATAN TUMINTING, MANADO - Angelyk Y. F. Kawalo; Charles R. Ngangi; Agnes E. Loho (Sam Ratulangi University, 2016)
Objective of this research was to assess the survival mechanism scavenger in landfills Sumompo, Tuminting Village District of Manado. Location of research is determined by purposive sampling while sample are scavengers who had worked more than 10 years as many as 15 people. Secondary data were obtained from the office of the Department of Sanitation, Parks and Office of Manado City and the Sumompo village Office. The analytical method used is descriptive statistics. The results showed that survival mechanism scavengers in landfill sites Sumompo based on food needs, performed with diet twice a day morning and afternoon with a fried or steamed fish and sometimes with vegetables. Based on the needs of clothing, they bought clothes once a year or of giving people and others acquired from landfills. Almost of scavengers home are made from plywood with a size of 20 m2 to 42 m2. Income ranges from Rp 1,000,000 to Rp 1886 666. Equipment purchased in most homes and others obtained from trash.